Pemanfaatan Virtual Reality dalam Simulasi Percobaan Hukum Ohm - Mabruroh, Faizatul; Talakua, Prisilia; Suhendi, Herni Yuniarti; Maipauw, Musa Marsel (Jurnal Pendidikan dan Ilmu Fisika, 2025)
This study aims to analyze the utilization of virtual reality (VR) technology in simulating Ohm's Law experiments in physics education. Ohm's Law is a fundamental concept in physics that relates voltage, current, and resistance in electrical circuits, which is essential for understanding various electrical phenomena. However, conventional physics experiments are often limited by the availability of equipment, infrastructure, and costs. Virtual reality offers a solution by providing immersive and interactive simulations, allowing students to conduct experiments without physical constraints. This study employs literature review approach to evaluate trends in the use of VR in Ohm's Law experiments. The results show that VR technology can enhance students' understanding of abstract physics concepts, increase engagement and motivation, and offer more flexible and safer access to physics experiments. This study also notes that combining real and virtual experiments yields better results than relying on one type of experiment. Therefore, the use of VR in physics education holds significant potential to overcome existing limitations and support more effective and engaging learning.